2021
DOI: 10.1007/s10334-021-00970-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of emulsifiers for the formation of oil-in-water emulsions: stability of the emulsions within 9 h after production and MR signal properties

Abstract: Objective To provide a basis for the selection of suitable emulsifiers in oil-in-water emulsions used as tissue analogs for MRI experiments. Three different emulsifiers were investigated with regard to their ability to stabilize tissue-like oil-in-water emulsions. Furthermore, MR signal properties of the emulsifiers themselves and influences on relaxation times and ADC values of the aqueous phase were investigated. Materials and methods Polysorbate 60, sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Importantly, they report on different lengths and timescales and so report on different aspects of the molecular dynamics involved in stabilizing the Pickering emulsions. Unlike the surfactants in molecular-based oil-inwater emulsions, which altered the T 1 , T 2 , and ADC of water depending on the concentrations, 20 those relaxation and diffusion properties of the serum layer were consistent with each bulk sample regardless of the CNF concentration and storage time. The T 1 distribution in the d-CNF emulsion layer changed over one month of storage, indicating microstructural changes such as flocculation and coalescence.…”
Section: ■ Conclusionmentioning
confidence: 89%
See 2 more Smart Citations
“…Importantly, they report on different lengths and timescales and so report on different aspects of the molecular dynamics involved in stabilizing the Pickering emulsions. Unlike the surfactants in molecular-based oil-inwater emulsions, which altered the T 1 , T 2 , and ADC of water depending on the concentrations, 20 those relaxation and diffusion properties of the serum layer were consistent with each bulk sample regardless of the CNF concentration and storage time. The T 1 distribution in the d-CNF emulsion layer changed over one month of storage, indicating microstructural changes such as flocculation and coalescence.…”
Section: ■ Conclusionmentioning
confidence: 89%
“…Several recent studies demonstrated that the distributions of water or fat with varying T 1 and/or T 2 relaxation times as visualized in MRI maps allowed evaluation of creaming and gravitational separation. , MRI and NMR are also useful for analyzing industrial emulsions such as for measuring droplet size distributions . Fritz et al investigated ADC values of water in oil-in-water emulsions emulsified with three different molecular surfactants. They suggested that the surfactant limits the water mobility and the degree of limitation depends on the surfactants and their concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soy lecithin was used as an emulsifier to obtain stable and homogenous emulsions. 23 The tubes were placed in horizontal direction in a water bath. Sequence parameters were identical to the in vivo measurements except TR, which was set to 20 msec to avoid T1-bias.…”
Section: Methodsmentioning
confidence: 99%
“…Emulsions were prepared in CELLSTAR polypropylene tubes (Greiner Bio‐One, Frickenhausen, Germany) with a volume of 50 mL, filled with distilled water and peanut oil. Soy lecithin was used as an emulsifier to obtain stable and homogenous emulsions 23 . The tubes were placed in horizontal direction in a water bath.…”
Section: Methodsmentioning
confidence: 99%